An overview on magnetic field and electric field interactions with ice crystallisation; application in the case of frozen food - Jha, Piyush Kumar; Xanthakis, Epameinondas; Jury, Vanessa; LeBail, Alain (My University, 2017)
Ice nucleation is a stochastic process and it is very difficult to be controlled. Freezing technologies and more specifically crystallisation assisted by magnetic, electric and electromagnetic fields have the capability to interact with nucleation. Static magnetic field (SMF) may affect matter crystallisation; however, this is still under debate in the literature. Static electric field (SEF) has a significant effect on crystallisation; this has been evidenced experimentally and confirmed by the theory. Oscillating magnetic field induces an oscillating electric field and is also expected to interact with water crystallisation. Oscillating electromagnetic fields interact with water, perturb and even disrupt hydrogen bonds, which in turn are thought to increase the degree of supercooling and to generate numerous fine ice crystals. Based on the literature, it seems that the frequency has an influence on the above-mentioned phenomena. This review article summarizes the fundamentals of freezing under magnetic, electric and electromagnetic fields, as well as their applicability and potentials within the food industry.
Keywords: Food preservation; Freezing; Electric field; Magnetic field; Supercooling